DESKRIPSI PRODUK PATISERI DAN ROTI DI TOKO IVARRA PATISSERIE & SUNG COFFEE PADANG - Mahdy, Muhammad Hasnul; Asnur, Lise (Komunitas Manajemen Kompetitif, 2024)
This research was motivated by bakery products and bakery products and this type of research was quantitative and descriptive using survey methods. The research was conducted at Ivarra Patisserie and Sung Cafe in Padang. The sample number was 94 people using purposive sampling techniques. Likert scale questionnaires were used to collect data. Descriptive statistical analysis and classification of interval class scores using the SPSS program version 25.00 were used as technical analyses.The overall result was 85.16 in the good category. brownies proved the results of 28.58 with the category quite good, Eclair by showing results of 24.32 with the category quite good, pizza showed results of 30.78 with the category quite good It can be concluded that the patisserie and bread products at the Ivarra patisserie & Sung Coffee Padang store are quite good and able to provide satisfaction to every consumer who comes.